Index of Short Stories in Literary Journals Published Between 1938-1950 in Turkey - Yener, Melih (İstanbul Üniversitesi, 2022)
Index of Short Stories in Literary Journals Published Between 1938-1950 in Turkey

Türkiye’de 1938-1950 Yılları Arasında Yayımlanmış Edebiyat Dergilerindeki Telif Hikâyeler Dizini
Türkiye’de 1938-1950 Yılları Arasında Yayımlanmış Edebiyat Dergilerindeki Telif Hikâyeler Dizini